Personality does not influence exercise-induced mood enhancement among female exercisers - Milton, K. E.; Lane, A. M.; Terry, P. C. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The present study investigated the influence of personality on exercise-induced mood changes. It was hypothesised that a) exercise would be associated with significant mood enhancement across all personality types, b) extroversion would be associated with positive mood and neuroticism with negative mood both pre- and post-exercise, and c) personality measures would interact with exercise-induced mood changes. Methods: Participants were 90 female exercisers (M=25.8 y, SD=9.0 y) who completed the Eysenck Personality Inventory once and the Brunel Mood Scale before and after a 60-min exercise session. Median splits were used to group participants into 4 personality types: stable introverts (n=25), stable extroverts (n=20), neurotic introverts (n=26), and neurotic extroverts (n=19). Results: Repeated measures MANOVA showed significant mood enhancement following exercise across all personality types. Neuroticism was associated with negative mood scores pre- and post-exercise but the effect of extroversion on reported mood was relatively weak. There was no significant interaction effect between exercise-induced mood enhancement and personality. Conclusion: Findings lend support to the notion that exercise is associated with improved mood. However, findings show that personality did not influence this effect, although neuroticism was associated with negative mood.